Learning descriptive text interactively: Combining the students’ creativity and writing skills for Phase D - Oktavia, Candrika Nur; Wulandari, Yosi; Miladika, Nashuka (Universitas Ahmad Dahlan, 2024)
Teaching descriptive texts at the junior high school level, particularly in Grade 7, often encounters challenges in creating an interactive and inclusive learning environment, especially for students with special needs. This study aims to explore and analyze effective interactive learning strategies for teaching descriptive texts, with a particular focus on technology integration, adaptations for special needs students, and comprehensive evaluation methods. Using a literature review approach, this article examines recent sources from educational journals, textbooks, and scholarly publications in the fields of Indonesian language instruction, educational technology, and inclusive education. The discussion addresses fundamental concepts of descriptive texts, interactive learning strategies such as the use of visual and audio media, group activities, language games, and the integration of technology into the learning process. The findings indicate that interactive learning approaches which incorporate technology and address students’ diverse needs significantly enhance descriptive writing skills, creativity, and student engagement. In conclusion, implementing interactive learning strategies in teaching descriptive texts not only improves students' academic abilities but also fosters critical thinking and social skills, ultimately creating a more inclusive and meaningful learning experience for all students.